2006
DOI: 10.1182/blood-2005-09-3640
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of c-KIT mutations in core binding factor leukemias: an Italian retrospective study

Abstract: Distinct forms of tyrosine kinase domain (TKD), juxtamembrane domain, exon 8, and internal tandem duplication (ITD) mutations of c-KIT, were observed in about 46% of core binding factor leukemia (CBFL) patients. To evaluate their prognostic significance, 67 adult patients with CBFL were analyzed to ascertain the c-KIT mutation status. In acute myeloid leukemia (AML) with t(8;21), the presence of c-KIT TKD mutation at codon 816 (TKD 816 ) was associated with a high white blood cell count at diagnosis (median, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
287
7
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(313 citation statements)
references
References 29 publications
13
287
7
6
Order By: Relevance
“…Authors suggested that the different gene profiling may lead to an enhancement of proliferation in the KITmutated cases, which may be reflected in the higher blast counts of those patients [43]. The clinical observations that affected patients with t(8;21) appear to have a higher WBC count and WBC-index at presentation and a higher frequency of EML might support this hypotheses [30,39,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors suggested that the different gene profiling may lead to an enhancement of proliferation in the KITmutated cases, which may be reflected in the higher blast counts of those patients [43]. The clinical observations that affected patients with t(8;21) appear to have a higher WBC count and WBC-index at presentation and a higher frequency of EML might support this hypotheses [30,39,45].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were enrolled in intensive chemotherapy protocols, as previously described [30]. In brief, they received a standard induction therapy with an anthracycline-containing regimen, most commonly the "713" regimen with cytarabine in 7-day continuous intravenous infusion and three doses of anthracycline (idarubicin 12 mg/m 2 /day or daunorubicin 60 mg/m 2 /day) or the "ICE" schedule, including etoposide 100 mg/m 2 /day on days 1-5.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular genetic investigation also revealed that receptor tyrosine kinase (RTK) gene mutations may impact outcome in patients with AML with t(8;21). [21][22][23][24] To further investigate the role of previously identified prognostic indicators in AML with t(8;21), particularly cytogenetic findings, in light of the advances in the past decade, we examined 56 cases of AML with t(8;21) diagnosed and treated in our hospital from May 1995 to July 2005. We reviewed the cytogenetic data of each case in the context of the overall clinicopathologic presentation and correlated the results with overall survival.…”
mentioning
confidence: 99%
“…Mutations of epigenetically related molecular events (DNMT3A, IDH1/2, TET2, ASXL1, and MLL) may suggest the possible benefit of epigenetictargeted therapy. In CBF AML, mutations in c-KIT have been reported to be associated with an adverse prognosis in some series [39][40][41]. The addition of a c-KIT inhibitor (dasatinib) to chemotherapy may have therapeutic benefits in c-KIT-mutated CBF AML [42].…”
mentioning
confidence: 99%